Psychological, social, and situational factors associated with COVID‐19 vaccination intentions: A study of UK key workers and non‐key workers. Issue 1 (5th May 2021) - Butter, Sarah; McGlinchey, Emily; Berry, Emma; Armour, Cherie
Abstract : Objectives: Vaccine hesitancy is a growing concern and threat to public health. This research will begin to examine the relative influence of relevant psychological, social, and situational factors on intent to engage with a hypothetical COVID‐19 vaccine among key workers and non‐key workers. Design: Cross‐sectional. Methods: The study utilized a sample of UK adults who completed the 1‐month follow‐up of The COVID‐19 Psychological Wellbeing Study during April/May 2020 and indicated having not been previously diagnosed with COVID‐19 (key workers n = 584; not key workers n = 1, 021). These groups were compared in relation to their intentions to vaccinate, perceived risk of infection, and symptom severity. Binary logistic regression was used to examine predictors of vaccine hesitancy. Results: Overall, 74.2% of the sample (76.2% key workers, 73.1% non‐key workers) indicated they would accept a COVID‐19 vaccine in future. Key workers (in particular health and social care workers) had a higher perceived risk of becoming infected in the coming months. For key workers, being female and perceiving oneself as having relatively low infection risk in the next 6 months was associated with increased likelihood of vaccine hesitancy. For non‐key workers, however, being aged 25–54, having a low or average income and not knowing someone diagnosed with COVID‐19 were associated with hesitancy. Conclusions: The proportion of individuals willing to accept a vaccine is encouraging but there is much room for improvement. Given the unique predictors of vaccine hesitancy in each group, public health campaigns may benefit from targeted messaging.